Why is Old Workers' Labor Market More Volatile? Unemployment Fluctuations over the Life-Cycle - Jean-Olivier Hairault; François Langot; Thepthida Sopraseuth (Institute for the Study of Labor (IZA), 2014)
Since the last recession, it is usually argued that older workers are less affected by the economic downturn because their unemployment rate rose less than the one of prime-age workers. This view is a myth: older workers are more sensitive to the business cycle. We document volatilities of worker flows and hourly wage across age groups on CPS data. We find that old worker's job flows are characterized by a higher responsiveness to business cycles than their younger counterparts. In contrast, their wage cyclicality is lower than prime-age workers'. Beyond this empirical contribution, we show that a life-cycle Mortensen & Pissarides (1994) model is well suited to explain these facts: older workers' shorter work-life expectancy endogenously reduces their outside options and leads their wages to be less sensitive to the business cycle. Thus, in a market where wage adjustments are small, quantities vary a lot: this is the case for older workers, whereas the youngest behave like infinitively-lived agents. Our theoretical results point out that Shimer (2005)'s view on the MP model is consistent with prime-age workers' labor market while aging endogenously introduces real wage rigidities, allowing to match what we observe for old workers, without specific assumptions as in Hagendorn & Manovskii (2008).
Keywords: E32; J11; J23; 330; search; matching; business cycle; life-cycle